Discovering COX-2 Inhibitors from Flavonoids and Diterpenoids - Jutti Levita, Muhammad Riza Rositama, Nazura Alias, Nurul Khalida, Nyi Mekar Saptarini, Sandra Megantara (Journal of Applied Pharmaceutical Science, 2017)
Cyclooxygenase is the enzyme that catalyzes the biosynthesis of prostaglandins from its substrate, arachidonic acid (AA). The reactions involve two steps which are (1) the oxidation of AA to the hydroperoxyendoperoxide PGG2, followed by (2) its subsequent reduction to the hydroxyl endoperoxide PGH2. Selective COX-2 inhibitors do not bind to Arg120, an amino acid residue used by AA and by the nonselective NSAIDs, all of which are carboxylic acids. In this work we studied the interaction of 54 compounds against COX enzymes for anti-inflammatory discovery using molecular docking simulation. Docking simulation for each compound was repeated 100x using Linux script command for AutoDockVina embedded in MGLTools v.1.5.6. Discovery Studio v.2.5.5 was employed to predict the volume of both COX binding pockets.21 compounds were selected according to their best scoring values and were calculated their selectivity index (cSI). Selective COX-2 inhibitors, respectively, are (1) 3,19-O-diacetylandrographolide; (2) 2-((1R,4aS,5R,6R,8aS)-6-hydroxy-5-(hydroxymethyl)-5,8a-dimethyl-2 methylene decahydronaphthalen-1-yl)-1-(2-oxo-2,5-dihydrofuran-3-yl) ethyl 4-methylbenzoate; and (3)12,13-dihydroandrographolide. Preferential COX-2 inhibitorsare (1) coronarin D; (2) 19-O-acetylhydroandrographolide; (3) p-methoxycinnamic acid; (4) kaempferide. The rest of the ligands are categorized as non-selective inhibitors.
Keywords: Anti-inflammatory, arachidonic acid, cyclooxygenase, NSAIDs, binding mode, NSAIDs, PGH, prostaglandin.